Remember, is it living? - Recavarren, Margarita (2003)
During the period of pain and blood that devastated our country starting in 1980, the Andean zone was the most affected, both because of the high number of its peasants killed and because of the high number of civilians affected and the destruction of its precarious infrastructure.